1938
DOI: 10.1017/s0007485300026286
|View full text |Cite
|
Sign up to set email alerts
|

Notes on the Insect Enemies of Chermes with particular Reference to Pineus pini, Koch, and P. strobi, Hartig

Abstract: Pineus pini has been introduced by accident into Australia and has become a pest of some importance on Pinus radiata and P. pinaster and also attacks a few other species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

1939
1939
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 2 publications
1
37
0
Order By: Relevance
“…Predators were only observed feeding on immature or adult adelgids, never directly on eggs. It was assumed they also fed on eggs, perhaps secondarily, because many were found inside of woolly masses and many of the predators are documented as predators of adelgid eggs (Wilson 1938, Smith and Coppel 1957, Amman 1966.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Predators were only observed feeding on immature or adult adelgids, never directly on eggs. It was assumed they also fed on eggs, perhaps secondarily, because many were found inside of woolly masses and many of the predators are documented as predators of adelgid eggs (Wilson 1938, Smith and Coppel 1957, Amman 1966.…”
Section: Resultsmentioning
confidence: 99%
“…Together, these three groups of insects comprised 81% of all individuals collected in all three sites in both twig and beat samples. Representatives of these groups and many of the individuals collected in this study are known predators of the family Adelgidae (Wilson 1938, Smith and Coppel 1957, Amman 1966, Harris 1973, Tedders and Schaefer 1994.…”
Section: Discussionmentioning
confidence: 99%
“…and S. (Hemiptera: Adelgidae) in the Himalayas. Wilson (1938) reared Melanips longitarsus (Amblynotus Reinhard) from puparia of Neoleucopis obscura (Haliday) (Chamaemyiidae), a predator of Pineus spp. (Hemiptera: Adelgidae), in England.…”
Section: Discussionmentioning
confidence: 99%
“…Two species of Chamaemyiidae (Diptera) that are specialist predators of adelgids, Leucopis argenticollis (Zetterstedt: Chamaemyiidae) and L. atrifacies (Aldrich), were abundant and seemed to be synchronized with the A. tsugae life cycle (McAlpine and Tanasijtshuk 1972, Greathead 1995, Tanasijtshuk 2002, Kohler et al 2008). However, several species of Chamaemyiidae that feed on adelgids, including Leucopis spp., have been shown to be susceptible to parasitism by Þgitid and pteromalid (Hymenoptera) pupal parasitoids, which could limit their effectiveness as biological control agents (Wilson 1938, Brown and Clark 1956, Mitchell 1962, Rao and Ghani 1972. In the process of rearing immature A. tsugae predators in the laboratory for our predator study, we observed several parasitoid species emerging from the puparia and cocoons of dipteran and neuropteran predators, including Leucopis spp.…”
mentioning
confidence: 99%
“…Wilson (1938) Barnes et al, 1976) recommended that Leucopis sp. nov. should be used for this purpose since the fly is widespread on Pineus spp.…”
Section: Controlmentioning
confidence: 99%